2012
DOI: 10.1089/ars.2011.4292
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Aberrant NADPH Oxidase Activity in Blood-Derived Mononuclear Cells from Type II Diabetes Mellitus Patients by a Naturally Fermented Papaya Preparation

Abstract: Supplementation of standardized fermented papaya preparation (FPP) to adult diabetic mice improves dermal wound healing outcomes. Peripheral blood mononuclear cells (PBMC) from type II diabetes mellitus (T2DM) patients elicit a compromised respiratory burst activity resulting in increased risk of infections for the diabetic patients. Aims: The objectives of the current study were to determine the effect of FPP supplementation on human diabetic PBMC respiratory burst activity and to understand underlying mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Recently, our laboratory reported the first experimental evidence demonstrating that FPP may improve diabetic wound outcomes by specifically influencing the response of wound-site macrophages and the subsequent angiogenic response (3). Furthermore, our ex vivo work demonstrated that FPP may correct deficiencies in respiratory burst capacity of peripheral blood mononuclear cells (PBMC) of type 2 diabetes mellitus (T2D) patients (6). The objectives of this study Innovation T2D patients are known to suffer from compromised respiratory burst function, making them vulnerable to infection-related complications.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, our laboratory reported the first experimental evidence demonstrating that FPP may improve diabetic wound outcomes by specifically influencing the response of wound-site macrophages and the subsequent angiogenic response (3). Furthermore, our ex vivo work demonstrated that FPP may correct deficiencies in respiratory burst capacity of peripheral blood mononuclear cells (PBMC) of type 2 diabetes mellitus (T2D) patients (6). The objectives of this study Innovation T2D patients are known to suffer from compromised respiratory burst function, making them vulnerable to infection-related complications.…”
Section: Introductionmentioning
confidence: 85%
“…FPP is safe for T2D patient consumption FPP possesses potent antioxidant activity (1). Our studies with T2D subjects demonstrated a beneficial effect of the supplement ex vivo on monocyte respiratory burst activity (6). This study was performed to determine whether FPP can confer a similar beneficial effect on monocytes when supplemented orally to T2D patients.…”
Section: Introductionmentioning
confidence: 98%
“…Peripheral blood mononuclear cells are established sources for determination of NADPH oxidase activity [27,28]. Blood from healthy volunteers was centrifuged at 150 9 g for 10 min at 20°C.…”
Section: Isolation and Preparation Of Mononuclear Leucocytesmentioning
confidence: 99%
“…The NADPH oxidase was obtained from the cell membranes of the mononuclear leucocytes after 3 freeze-thawing cycles. Peripheral blood mononuclear cells are established sources for determination of NADPH oxidase activity [27,28].…”
Section: Isolation and Preparation Of Mononuclear Leucocytesmentioning
confidence: 99%
“…This is important because both elevated oxidative stress and mitochondrial dysfunction can lead to increased apoptosis in CKD monocytes (Dounousi et al, 2012) and tissues. Interestingly, the oxidative burst, which is necessary for innate immunity, is suppressed in diabetics suggesting that decreased oxidative burst activity could be related to the severity of renal dysfunction (Dickerson et al, 2012), a suppressed immune response, accumulation of damaged monocytes, and disease pathology. It is clear that mitochondrial homeostasis and gene expression is perturbed in immune cells during diabetes and is likely a critical factor in the development of atherosclerosis in these patients.…”
Section: Function Of Monocytes and Macrophages In Pathologymentioning
confidence: 99%